PENGEMBANGAN MODUL FISIKA ONLINE BERBASIS WEB PADA POKOK BAHASAN KINEMATIKA GERAK LURUS (PHYSICS OF ONLINE WEB-BASED MODULES KINEMATICS ON THE SUBJECT STRAIGHT MOTION) - Rahmawati Rahmawati; I Made Astra; Dwi Susanti (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2012)
This study aims to develop online learning media in the form of modules on the subject of kinematics motion straight. The research method used is the development of research methods (research and development) with a groove 1) analysis of needs, 2) making an online module 3) testing of the module by material experts and media experts 4) testing modules by teachers and students. The quality of media according to experts both from the media fascination with the module and the module content averages 72%. The quality of media according to experts from both the material aspect of the feasibility of content, language, and presentation by the average percentage of 79%. And quality of media according to the teachers and students also are in the category with the average percentage of 76% sequentially and 77%. Based on this research, the media online learning physics in the form of a web-based modules on the subject of a straight motion kinematics can be used as a medium of self-learning for vocational classes X semester 1 in accordance with the standards of competence, basic competence, and learning indicators. Key Words: Phisic online module; kinematics of motion straight.